Hubungan Lingkar Lengan Atas (Lila) dengan Kejadian Anemia pada Ibu Hamil di Wilayah Kerja Puskesmas Tallunglipu Tahun 2021 - Eka Fadillah Bagenda; Irmayanti A. Oka; Sri Devi Syamsuddin (Neolectura, 2022)
The gestation period starts from conception until the birth of the fetus, where the normal length of pregnancy is 280 days or 40 weeks or 9 months 7 days calculated from the first day of the last menstruation. Anemia is a decreased level of hemoglobin and the number of red blood cells below the normal value set for individuals. LILA measurement is a way to determine the risk of protein energy deficiency (PEM) in women of childbearing age (WUS). General Objectives It is known the relationship between upper arm circumference (LILA) and the incidence of anemia in pregnant women at the Tallunglipu Health Center in 2021.This research method uses a Cross Sectional Study approach. The sampling technique used was purposive sampling. The population in this study was 65 pregnant women. The samples in this study were pregnant women with anemia who came to the Tallunglipu Health Center for the period November - December 2021, as many as 30 people. Bivariate analysis was carried out on each dependent and independent variable using the Fisher's Exact Test. the results of the Fisher's Exact Test showed the value of P = 0.006 with a significant level of = 0.05. The results showed that there was a relationship between upper arm circumference (LILA) and the incidence of anemia in pregnant women. North Toraja needs to be more intensively carried out by health workers.